Relation between Leadership Style and Personality Type of Zillenials, Based on the Myers-Briggs Model - Bodnar, Jakub (Relacja między stylem przywództwa a typem osobowości Zillenialsów na podstawie modelu Myers-Briggs, 2025)
The paper examines the relationship between leadership styles and personality types among Zillenials, a microgeneration bridging Millennials and Generation Z. The primary goal is to determine whether a dominant personality type exists among Zillenials and to assess the presence of different leadership styles in their preferences. Additionally, the study explores whether individuals with similar personality traits tend to favour the same leadership style. To address these objectives, an online survey was conducted, which included demographic questions, statements about leadership styles rated on a Likert scale, and an externally sourced personality test based on the MBTI model. The findings suggest that leadership style preferences align more closely with generational characteristics than specific personality types. Transformational leadership emerged as the most preferred, while Autocratic and Laissez-faire styles received minimal support. The most common personality type identified was INFP, reinforcing Zillenials’ emphasis on inclusivity, authenticity, and personal values. These insights contribute to understanding how personality and generational traits influence workplace dynamics, offering valuable implications for leadership development and organizational strategies.
Quote as: Bodnar, J. (2024). Relation between Leadership Style and Personality Type of Zillenials, Based on the Myers-Briggs Model. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 23-35). Publishing House of Wroclaw University of Economics and Business.
Keywords: leadership style; personality type; Myers-Briggs; Zillenials; styl zarządzania; typ osobowości; Zillenialsi